Neutrophil Gelatinase-Associated Lipocalin: Its Response to Hypoxia and Association with Acute Mountain Sickness. Issue 5 (20th October 2013) - Mellor, Adrian; Boos, Christopher; Stacey, Mike; Hooper, Tim; Smith, Chris; Begley, Joe; Yarker, Jo; Piper, Rick; O'Hara, John; King, Rod; Turner, Steve; Woods, David R.
Abstract : Acute Mountain Sickness (AMS) is a common clinical challenge at high altitude (HA). A point-of-care biochemical marker for AMS could have widespread utility. Neutrophil gelatinase-associated lipocalin (NGAL) rises in response to renal injury, inflammation and oxidative stress. We investigated whether NGAL rises with HA and if this rise was related to AMS, hypoxia or exercise. NGAL was assayed in a cohort (n = 22 ) undertaking 6 hours exercise at near sea-level (SL); a cohort (n = 14 ) during 3 hours of normobaric hypoxia (FiO2 11.6%) and on two trekking expeditions (n = 52 ) to over 5000 m. NGAL did not change with exercise at SL or following normobaric hypoxia. During the trekking expeditions NGAL levels (ng/ml, mean ± sd, range) rose significantly (P < 0.001 ) from 68 ± 14 (60–102) at 1300 m to 183 ± 107 (65–519); 143 ± 66 (60–315) and 150 ± 71 (60–357) at 3400 m, 4270 m and 5150 m respectively. At 5150 m there was a significant difference in NGAL between those with severe AMS (n = 7 ), mild AMS (n = 16 ) or no AMS (n = 23 ): 201 ± 34 versus 171 ± 19 versus 124 ± 12 respectively (P = 0.009 for severe versus no AMS;P = 0.026 for mild versus no AMS). In summary, NGAL rises in response to prolonged hypobaric hypoxia and demonstrates a relationship to the presence and severity of AMS.